THE IMPACT OF THE COVID-19 PANDEMIC ON HUNGARIAN HEALTH TOURISM - NAGY, Tamás; LACZKÓ, Tamás; BÁTOR, Gábor László; EMŐDY, Barnabás (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2023)
Introduction: Health tourism is a key economic sector in Hungary, and its development and support has been a priority of the national economic development programmes since the millennium. Just like in the rest of the world, Hungary’s tourism performed badly in the first year of the COVID-19. Objective: The objective of our study was to examine the main indicators of inbound health tourism to Hungary in the period of 2019-2020. Our main objective was to estimate the loss to the country’s budget from declining inbound health tourism. Methods: The applied research method was secondary research, based on tourism demand data published by the Central Statistical Office (KSH). The national economic effects generated by the expenditure of foreign health tourists in Hungary were estimated using input-output analysis. Results: The number of foreign health tourists decreased to 46.4% compared to 2019, and the number of days spent by foreign health tourists decreased to 40.9% compared to the previous year. In the year of the pandemic, inbound health tourist spending generated total national output of €417 million, a decrease of more than 46% compared to the previous year. The contribution of inbound health tourism to GDP was €209.2 million, almost €160 million lower than in 2019. Conclusion: After a peak year in 2019, pandemic COVID-19 led to a significant drop in demand in the inbound health tourism market, which will also see a sectoral and territorial shift in 2020. Received 2023 April 04; Revised 2023 June 15.; Accepted 2023 June 16; Available online 2023 July 30; Available print 2023 August 30.